MENGENAL I’JAZUL QURAN: PERSPEKTIF KLASIK DAN KONTEMPORER - Fauzan Delasta Bramantyo; Andi Muhammad Akmal, Hamka Ilyas (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This research aims to explore and understand more about Getting to Know the Quran: Classical and Contemporary Perspectives. This research is a Descriptive Qualitative research, this research tries to study and explore I'jazul Qur'an in a classical and contemporary perspective. This type of research is library research where the author collects and reviews material from books, articles, and other sources relevant to the theme. The results of the study show that in the classical perspective, i'jazul Qur'an is understood as the sanctity of the Qur'an from all flaws, shortcomings, and errors. Some of the evidence of I'jazul Qur'an according to the classical perspective includes Fasahah and Balaghah, Scientific Miracles, Miracles of Prophecy, Spiritual Influence, Affirming the Authenticity of the Qur'an, Increasing Belief, Challenging Thinkers. Some of the emphasis of I'jazul Qur'an according to contemporary perspectives include I'jazul Qur'an and Modern Science, I'jazul Qur'an and Morality, I'jazul Qur'an and Morality. and I'jazul Qur'an and Modern Challenges. The Implications of I'jazul Qur'an in the Life of Muslims Today are Strengthening Faith, Motivation to Learn and Work, and Character and Moral Formation. Another conclusion is that the concept of i'jazul Qur'an is still relevant to today's life. In the era of globalization and religious pluralism, this concept still has an important role in defending Islamic values and promoting interreligious tolerance.